(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2008)
An exposition is provided from a reformational perspective of the short term dimension (situational dimension) of the leadership role of the educator. The short term dimension is discussed in relation to the characteristics of the leader, the characteristics of the followers and the characteristics of the situation in which leadership is provided. Under each of these characteristics several factors are shortly highlighted and explained.